Edukace u schizofrenie: Jak pacienti a príbuzní hodnotí program prevence relapsu PREDUKA - Motlová, Lucie Bankovská; Dragomirecká, Eva; Matelová, Sárka; Otevrelová, Renata; Cermáková, Radka; Cermák, Jan; Lednická, Eva; Hegedüsová, Renata; Hübsch, Tomás; Rothanzlová, Sona; Tomesová, Martina; Spaniel, Filip; et al. (Casopis lekaru ceskych, 2010)
Antipsychotic medication and early relapse warning signs detection are the cornerstone of relapse prevention in schizophrenia spectrum disorders. Many patients do not use antipsychotic medication because of lack of information about its preventive effects and the risk of relapse. We introduce PREDUKA--PREventive EDUcational programme for relapse prevention. The goal of the programme is to deliver the information about schizophrenia to patients and their relatives. 178 patients and 252 relatives (118 mothers and 51 fathers) took part in 25 one-day psychoeducational programmes in 6 centres in the Czech Republic between January 2008 and June 2009 and anonymously fulfilled a short questionnaire. Patients and relatives assessed the programme with an average mark 1.4 (1 best, 5 worst). 49.4% patients and 49.0% relatives had received enough information about psychotic disorders during their hospitalization. Moreover 94.1% patients and 95.7% relatives confirmed acquiring new information on how to live with psychosis as a result of PREDUKA programme. 59.6% patients and 73.8% relatives were interested in ITAREPS - Information Technology Aided Relapse Prevention Programme. Mothers were significantly more interested (82.2%) than fathers (62.2%) (p = 0.031). Expressed high interest of patients and their relatives in both programmes indicates their readiness to become active and competent partners in the long-term treatment of schizophrenia spectrum disorders.
Keywords: schizofrenie; Schizophrenia; Recurrence; Patient Education as Topic; Educational Measurement; Adaptation, Psychological; výuka - hodnocení; vzdělávání pacientů jako téma; rodiče; Medication Adherence; lidé; Parents; adaptace psychologická; Humans; adherence k farmakoterapii; recidiva